Ekranisasi Novel Keluarga Cemara Karya Arswendo Atmowiloto Ke Film Keluarga Cemara Karya Sutradara Yandy Laurens - Diva Azkya Amalia Nurfadia; Dian Hartati (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
The purpose of this study is to compare the novel Keluarga Cemara by Arswendo Atmowiloto with the film Keluarga Cemara directed by Yandy Laurens using the ecranization theory. The research method used is descriptive qualitative method. Based on the results of the research, in this novel and film there are shrinking, adding, and changing variations. This happens because novels and films are different types of literary works because the presentation of the media is also different. Usually, novels cannot be read completely at one time. Of course, it has to take quite a lot of time, whereas in the film, the duration is only about 120 minutes. This short duration makes the director have to shrink, add and change variations of the story to support the success of the novel he is adapting.